Predicting supervisor capacities to foster higher forms of learning through undergraduate medical student research - Margaret MacDougall (Journal of the Scholarship of Teaching and Learning, 2014)
The credibility of short-term undergraduate research as a paradigm for effective learning within Medicine has been recognized. With a view to strengthening this paradigm and enhancing research-teaching linkages, this study explores whether particular types of research supervisor are pre-disposed to providing supportive learning environments.  Correspondingly, a novel solution is offered to addressing clinical governance concerns about failings in preparing students for a supercomplex world. While recommendations for addressing these concerns have previously focused on curriculum delivery and assessment, this study affords a fresh perspective through consideration of research supervisor attributes, behaviours and experiences.   Using statistical analyses of response data from a large cohort of experienced research supervisors who completed an online survey, evidence is found to suggest that staff involvement in personal research ought to enhance student learning through research. In turn, the supervisor factors which are most supportive of this effect may vary according to how we measure higher forms of learning. Supervisors are advised to design successive follow-on research projects to facilitate cross-disciplinary research. In preparing medical graduates for survival in a super-complex world, more needs to be done, however, to investigate why supervisors who see their students more regularly are more likely to provide cross-disciplinary research opportunities. By contrast, potential to engage in risk-taking behaviours and maintain or progress to an advanced stage of learning may originate more precisely with the student.